Resolution of ruptures in therapeuticalliance: Its role on change processes according to a relational approach - Coutinho,Joana (2009)
This article presents the basic theoretical assumptions of a Relational Approach to Psycho-therapy, particularly in what concerns the interpersonal roots of psychopathology and consequently the way the relational experience therapy provides, may serve to change the client’s dysfunctional interpersonal schema subjacent to symptoms. In the second part of the article we present the clinical implications of the concept of Ruptures in Therapeutic Alliance, seen as a tension or breakdown in the collaborative relationship between therapist and patient. Following Bordin’s conceptualization of the alliance, ruptures may consist of a disagreement about the tasks or the goals of treatment or a strain in the bond. The most important findings that have been collected about the way these interpersonal cycles between therapist and patient can lead to change when efficiently addressed, or to poor outcome or unilateral termination when unresolved, are reviewed. Having already accumulated enough evidence about the importance of the therapeutic alliance, a second generation of alliance researchers is now trying to understand the way the alliance is a mechanism of change. The findings we review suggest that the process of repairing weakened alliances may offer an answer to that question.